The Emergence of Somatic Psychology and Bodymind Therapy - Barratt, B. (Critical Theory and Practice in Psychology and the Human Sciences, 2010)
Somatic psychology and bodymind therapy (the simultaneous study of the mind and body) are challenging contemporary understandings of the psyche, of what it means to be human and how to heal human suffering.